Editorial JARER Volume 7 Issue 2 - Olaleye, Abel (Journal of African Real Estate Research, 2023)
Editorial Welcome to Volume 7 (2022), Issue 2 of the Journal of African Real Estate Research (JARER). JARER has been providing valuable resources and continues to be an exciting outlet for authors across Africa to propagate the results of their research activities. The journal has been strengthened and continues to grow in leaps and bounds. We are happy to inform our stakeholders that, JARER has been approved to be listed in the Directory of Open Access Journal (DOAJ) as from January, 2023. This is in addition to being recognised as meeting acceptable quality and listed in the 2021 American Real Estate Society’s (ARES) Real Estate Journal List. The list can be found at: https://www.aresnet.org/page/journal-list. We are not unaware that these achievements cannot be made possible without the efforts and support of the journal editorial board members, our anonymous reviewers and other stakeholders. Our gratitude therefore goes to them and all others stakeholders, including the African Real Estate Society’s board members, the team and colleagues at the Library services at the University of Cape Town, and the Journal Manager, Ms Lesedi Kgaka, who has been working diligently in managing the journal’s operations and at ensuring that the journal is moved forward to an enviable height. We will continue to appreciate the support from Prof. Karl-Werner Schulte and his team from the IREBS at Regensburg University, the IRES, and ERES. The journal’s qualities of review and thoroughness, no doubt, have improved tremendously, even though this has increased the rate of paper rejection, in the recent past. This explains why the current issue contains four papers with focus on private housing development, property rating valuation, price volatility in the stock market and void management strategies in multi-tenanted office property. This first paper examines the factors that influence access to urban land for private housing development in Minna, Nigeria. A total of 18 variables were distilled from previous empirical studies which were analysed using factor analysis technique. The results indicate that land titling, socio-economic characteristics of the populace and land acquisition issues were the main factors affecting urban land accessibility for private housing development. The study concludes that stakeholders in land administration and management in the city should work on these factors to improve access to land for private housing development. The second paper examines the volatility of the daily market price of listed property stocks on the Johannesburg Stock Exchange (JSE) for a 10-year period (2008-2017). The study used daily prices from January 2, 2008, to December 29, 2017, of twelve quoted property companies out of the twenty-seven listed on the Johannesburg Stock Exchange (SA REIT Association, 2020). The study modelled SA-REIT market price volatility using generalised autoregressive conditional heteroskedasticity (GARCH 1, 1). The result implies that investment in the property stock market is strongly driven by positive news on daily prices than a negative shock. The study thus concludes that South African property investors are more sensitive and exhibit a sharp response to good news on the daily market price than bad news when thinking of investing in listed property company shares. The focus of third paper is an investigation of the causes of variance in assessed rateable values among property rating valuers. Qualitative data were obtained from valuers and content analysis was carried out to analyse the data. Findings showed that specialisation, valuers’ opinion on the rating valuation input variables, lack of due diligence, corruption, the ambiguity of the rating law, information in the tone–of–the–list, lack of proper sanction and gratification by ratepayers are some of the causes of variance in rateable value. The conclusion drawn centres on the need to correct the identified problems causing variance in rating valuation with a view to ensuring effective rating administration. The fourth paper assesses void management strategies adopted by Estate Surveying firms in multi-tenanted office properties in Lagos, Nigeria. Data obtained were analysed using frequency table, mean, mean deviation and mean ranking. The study found that void eradication strategies of adherence to vacation clauses and regular advertisement were the most frequently used strategies. The paper concludes that choice of void management strategies in multi-tenanted office properties depends on the cost involved and effectiveness of the strategies. Thank you for your continued interest in JARER. I look forward to receiving your feedback on this and previous issues of the journal. Prof. Abel Olaleye Editor-in-Chief